(untitled) (Res Medica, 2014)
THE MENTAL STATE Numerous of the clinical signs characterizing the mental state of the patient will have become apparent during history taking. The clinician then has the opportunity to study any aspect of the psychological state which calls for special further evaluation. 1. General appearance and behaviour: The patient is described tersely but vividly, to provide a record which will suffice to call him to mind as he looked when in the examination room : his posture, his expression, his clothes, his mannerisms, his reactions to the clinician, and his mode of presenting himself. In the case of a mute or stuperose patient this aspect of the mental state may be among the most revealing. 2. Thought processes: Talk is externalized thought, thus the clinician notes how ideas are handled and the manner in which the patient arranges and expresses his concepts. The major pathology may be in this psychological sector, and be disclosed in disordered syntax : as when a schizophrenic patient juxtaposes apparently unrelated references to a portion of his body and the river he lived close to as a child : “This is my arm and the Couch is in Essex” .